2018
DOI: 10.1063/1.5025150
|View full text |Cite
|
Sign up to set email alerts
|

Note: On the dielectric constant of nanoconfined water

Abstract: Investigations of dielectric properties of liquid water in nanoconfinement are highly relevant for the energy storage in electrochemical systems, mineral-fluid interactions in geochemistry and microfluid based devices in biomedical analysis 1 . It has been reported that polarization shows a strong anisotropy at water interfaces 2,3 and the dielectric constant of nanoconfined water is surprisingly low ( ⊥ ∼ 10) 4 . Here, using a simple capacitor model, we show that the low dielectric constant of nanoconfined wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 12 publications
7
57
0
Order By: Relevance
“…Now using this value of δ and eq 11, we calculate the effective dielectric constant at different regions of water, which is given in Table 1. We observe a reduced effective dielectric permittivity for confined water, as reported in previous studies, 9,28 with the least value of permittivity shown by the interface regions. The low dielectric constant at the interface indicates that the interfacial water molecules restrain themselves from aligning along the direction of the external field.…”
Section: ■ Results and Discussionsupporting
confidence: 88%
“…Now using this value of δ and eq 11, we calculate the effective dielectric constant at different regions of water, which is given in Table 1. We observe a reduced effective dielectric permittivity for confined water, as reported in previous studies, 9,28 with the least value of permittivity shown by the interface regions. The low dielectric constant at the interface indicates that the interfacial water molecules restrain themselves from aligning along the direction of the external field.…”
Section: ■ Results and Discussionsupporting
confidence: 88%
“…67), the fact that dielectric properties can be understood within the LMFT framework can be viewed as a demonstration of this result and is perhaps more open to intuitive physical interpretation. This may prove useful as we continue to develop our understanding of dielectrics under confinement (1,4,9,10).…”
Section: Discussionmentioning
confidence: 99%
“…Their data were well fitted by a simple model of three capacitors in series made of a bulk layer (with a bulk value ⊥ 80) sandwiched between two thin layers of width 0.74 nm close to the surface. This low value of ⊥ may arise simply from an averaging that includes the thin layers of vacuum close to hydrophobic surfaces (of width equal to twice the van der Waals radius of wall atoms) with = 1, and a bulk value quickly reached in between (even for nanometric water slabs), as has been suggested by all-atom simulations [34].…”
Section: Introductionmentioning
confidence: 84%